An introduction to Literary Studies - Klarer, Mario, 1962- (Routledge, 2013)
In this classic beginner's guide to English literature, Mario Klarer offers a concise and accessible discussion of central issues in the study of literary texts, looking at:definitions of key terms such as literature and textthe genres of fiction, poetry, drama, and filmperiods and classifications of literaturetheoretical approaches to textsthe use of secondary resourcesguidelines for writing research essaysThe new and expanded edition is fully updated to include:a wider range of textual examples from world li.